Selling Behaviour in Installments from a Socio-Cultural and Islamic Perspective: A Case Study of the People of Bone-Bone Sub-district, South Sulawesi, Indonesia - Rosdiana, Erma; Lampe, Munsi; Hamka, Icha Musywirah; Sukriya, Aminata (Al-Amwal : Journal of Islamic Economic Law, 2024)
Purpose – This study aims to explain the installment sales behaviour of sellers in the Bone-bone community. Goods sold include clothing, kitchen utensils, motorbikes, and tupperware. Method – By using qualitative research methods with descriptive type of descriptive research, the researcher conducted an indept interview to obtain a comprehensive a comprehensive picture of installment activities. Data analysis was conducted whilst in the field and after the field. The data analysis technique used is qualitative analysis technique. Result – The findings of this study indicate that the promotion carried out by traders of two kinds, promotion in stores and traveling promotions. Implication – The implication of this research is to provide socialization education as a reference for community life transactions in accordance with Islamic law, then provide knowledge regarding the concept of transaction agreements in society.